ELABORACIÓN DE UN PLAN ESTRATÉGICO PARA LA EMPRESA “DIFAR” DE LA CIUDAD DE LOJA - Ojeda Matailo, María fernanda (2015)
This thesis was developed with the aim of promoting the development and growth of "DIFAR" dedicated to the distribution of national brewery in the city of Loja, in order to improve teamwork and proper decision-dictions. This study was conducted based theoretical underpinnings and field information obtained through the use of surveys performed to 138 customers, 30 employees and an interview with Supervisor. The research process starts from making a situational analysis of the company; to conduct user surveys and employees, the supervisor interview and direct observation, gave us an overview of current business conditions and their social environment. To do so first I perform an external analysis in the company, which allowed me to define the threats opportunities, just to or built the EFE matrix, wherein the weighted total is 2.39 indicating that the company if it is seizing opportunities to minimizes the impact of threats. Then by internal analysis of the company, the company diagnosis was made, and the strengths and weaknesses of it, which gave the matrix EFI weighted rating of the company is 2.65 that was developed was determined. With internal and external analysis SWOT matrix that allowed define the opportunities, threats, strengths and weaknesses, so that the array of high impact with what 6 we proceeded to perform the FO, DO, FA combination was built was built, DA obtaining as a result the strategic objectives. In order to correct the existential shortcomings, such as lack of strategies to increase the number of customers and sales, lack of corporate vision and mission, and the lack of strategies to promote this company are reasons for not allowing them to grow and generate more profitability for its partners, it has therefore proposed the "development of a strategic plan for the company" DIFAR "CITY OF LOJA" in order to improve existing services, get a good focus on citizenship efficient service, always aiming to achieve customer satisfaction. Within the proposed five strategic objectives which are built through a logical framework they were defined, in which notes the problem, the goal strategies and activities, policy makers, tactics and financing cost. The total cost amounts to which the implementation of this strategic plan is $ 8.975.00, value to be invested will allow the company to achieve improvement in their economic situation and reach higher levels of acceptance by customers, users and citizens in general. Finally the conclusions reached with the detailed analysis of the collected information are presented; if the recommendations that will be submitted for further socialization, knowledge and implementation.